THE ANALYSIS OF TOURIST CONSUMER'S PERCEPTION ON THE IMPORTANCE OF COMMERCIAL IN TOURISM - Carmen, IORDACHE; Alexandrina, SÎRBU (Strategii Manageriale)
The demarcation of perceptions with regard to ad's role in tourism means a typical process for contouring the positioning of tourism's product promoted in consumer's mind. For this reason, the construction of tourist commercials as a function of consumers' perceptions, but also the relationship which they have, reported to experience sensations that make up tourist, is essential in building a positive tourist images. In this respect, it has been carried out a quantitative marketing research, on a sample of 63 respondents, with the aim of knowing the perception against the main sources of information in the purchasing tourist product, the degree of involvement in the search for information on the tourist's product, the commercial influence on the promotion of tourist destinations, the main supports of the ad where they take over the information, the degree of involvement by type of advertising, sufficient information presented in a report, the relationship between the quality of ad's decision and the inspection, the elements which help to distinguish better the information on a tourist destination and the impact of provided informations by advertising about a tourist destination.